Prevalence and cardiac phenotype of patients with a phospholamban mutation - Hof, I. E.; van der Heijden, J. F.; Kranias, EG; Sanoudou, D.; de Boer, R. A.; van Tintelen, J. P.; van der Zwaag, P. A.; Doevendans, P. A. (Neth Heart JNeth Heart JNeth Heart J, 2019)
Pathogenic mutations in the phospholamban (PLN) gene may give rise to inherited cardiomyopathies due to its role in calcium homeostasis. Several PLN mutations have been identified, with the R14del mutation being the most prevalent cardiomyopathy-related mutation in the Netherlands. It is present in patients diagnosed with arrhythmogenic cardiomyopathy as well as dilated cardiomyopathy. Awareness of the phenotype of this PLN mutation is of great importance, since many carriers remain to be identified. Patients with the R14del mutation are characterised by older age at onset, low-voltage electrocardiograms and a high frequency of ventricular arrhythmias. Additionally, these patients have a poor prognosis often with left ventricular dysfunction and early-onset heart failure. Therefore, when there is a suspicion of a PLN mutation, cardiac and genetic screening is strongly recommended.